Upsurge in biomedical waste due to COVID-19 in India: A statistical correlation, challenges and recommendations - Khosla, Ritu; Jha, Ashima; Dua, Shweta; Varmani, Shivani G.; Rajput, Namita; Pani, Balaram (Frontiers in Environmental Science, 2022)
Proper management of Biomedical Waste (BMW) is an essential component of any sustainable healthcare sector. With the burst of COVID-19 pandemic when every hospital and treatment facility was overburdened patients, efficient handling of the huge amount of generated BMW became a task for the entire world. This review compares the BMW generated before and during the second wave of COVID-19, highlights the challenges in managing the exuberated amount of COVID-19 waste and sites recommendations to promote sustainable design thinking, in order to address this grave concern in the current setting of the Indian system. The study indicated that inappropriate management of waste and the lacunae in the entire chain from segregation to collection until its disposal has posed a serious threat to the wellbeing of health care workers, sanitation staff as well as the operators and housekeeping staff at the hospitals, isolation centers and Municipal Corporation. Many states had inadequate number of common BMW treatment facilities (CBMWTFs) leading to inefficient treatment of the excess waste. .The behavioural and attitudinal barriers of neglect and ignorance of different stakeholders further aggravated the problem of BMW management to manifolds., To achieve better management we recommend spreading awareness regarding the kind and infectious nature of waste generated by COVID-19 patients and their caregivers, segregation and decontamination of such waste at source and increasing the capacity as well as number of CBMWTFs. Creative ways to recycle the waste must be devised so as to reduce the burden on disposal sites.